Davies, Soviet Economic Development From Lenin To Khrushchev; Pearson, The Rise And Fall Of The Soviet Empire - Stevens, Carol (Teaching History: A Journal of Methods, 2000)
Each of these books is part of a series written to provide succinct and readable overviews of specialized topics "for students and their teachers." Between them, they provide a comprehensive picture of some very important elements of Soviet policy.